Pemanfaatan Tajwid Exploration Box Untuk Meningkatkan Kualitas Pengajaran Al Qur'an - Naya Ajeng Inayah; Luthfi Huwaidi; Najma Najma (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study aims to improve the quality of Tajwid learning at Nurul Islam Islamic Education Centre (TPA), Penggilingan, East Jakarta, through the use of an innovative learning medium called the Tajwid Exploration Box. The main issue identified was the limited availability of effective tajwid learning media, which resulted in students’ low understanding of Qur’anic recitation rules. This study employed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants involved were 17 individuals, including 13 students and 4 teachers. The effectiveness of the learning media was evaluated using pre-test and post-test scores, N-Gain analysis, and user response questionnaires. The results indicate a significant improvement in tajwid comprehension, with the average score increasing from 57.35 in the pre-test to 81.47 in the post-test, and an N-Gain value of 0.57, categorised as moderate. Furthermore, questionnaire findings revealed highly positive responses from both students and teachers, with an overall satisfaction rate of 93%, particularly in terms of media attractiveness, material usefulness, and learning atmosphere. These findings demonstrate that the Tajwid Exploration Box is an effective interactive learning medium that enhances students’ tajwid understanding while fostering learning motivation and independence. Therefore, this media can serve as an innovative alternative for tajwid instruction in non-formal Qur’anic educational institutions.